Development of Mineral Fertilizers From Agricultural Resources of Karakalpakstan for use in the Creation of the Forests on the Dried Bottom of the Aral sea - Khudoyberdiev Fazlidin Isroilovich, Tadjiev Sayfitdin , Tahirova Nargisa (International Journal of Advanced Science and Technology, 2020)
This article discusses the intensive processes of production of mineral fertilizers by acidifying glauconite sand with nitric acid, followed by processing low-grade phosphate raw materials with acidification products. This study proved that the introduction of phosphorites in the system improves the particle size distribution and quality of the finished product. When processing glauconite with incomplete norms of nitric acid, a complex fertilizer is obtained